How do healthcare professionals respond to ethical challenges regarding information management? A review of empirical studies. (1st January 2021) - Ewuoso, Cornelius; Hall, Susan; Dierickx, Kris
ABSTRACT: Aim: This study is a systematic review that aims to assess how healthcare professionals manage ethical challenges regarding information within the clinical context. Method and Materials: We carried out searches in PubMed, Google Scholar and Embase, using two search strings; searches generated 665 hits. After screening, 47 articles relevant to the study aim were selected for review. Seven articles were identified through snowballing, and 18 others were included following a system update in PubMed, bringing the total number of articles reviewed to 72. We used a Q-sort technique for the analysis of identified articles. Findings: This study reveals that healthcare professionals around the world generally employ (to varying degrees) four broad strategies to manage different types of challenges regarding information, which can be categorized as challenges related to confidentiality, communication, professional duty, and decision-making. The strategies employed for managing these challenges include resolution, consultation, stalling, and disclosure/concealment. Conclusion: There are a variety of strategies which health professionals can adopt to address challenges regarding information management within the clinical context. This insight complements current efforts aimed at enhancing health professional-patient communication. Very few studies have researched the results of employing these various strategies. Future empirical studies are required to address this.